A PARADIGM SHIFT IN INDONESIAN FORESTRY LAW: ANALYZING THE SECURITY APPROACH OF PRESIDENTIAL REGULATION NO. 5 OF 2025 - Ida Yulita Susanti (Proceeding International Conference on Social Sciences, 2026)
Forestry law enforcement in Indonesia faces chronic implementation challenges, rendering Law No. 41 of 1999 on Forestry ineffective in curbing the rates of deforestation and forest encroachment. This failure has created a momentum for the state to seek a policy breakthrough, which manifested in the issuance of Presidential Regulation No. 5 of 2025 concerning the Orderliness of Forest Areas. This research aims to critically analyze the paradigm shift and the philosophical tension arising between the Forestry Law as lex generalis and Presidential Regulation No. 5 of 2025 as a lex specialis intervention. Using a juridical-philosophical approach, this study examines the causal relationship between the phenomenon of institutional failure in civil law enforcement and the emergence of a policy response oriented towards a security approach. The main finding reveals that Presidential Regulation No. 5 of 2025 fundamentally alters the landscape of environmental law enforcement by establishing a Task Force predominantly led by the Minister of Defense and involving elements of the military (TNI) and police. Instead of strengthening the mandated civilian institution (Ministry of Environment and Forestry), this policy bypasses it, reflecting a symptom of "environmental securitization." This approach reduces the complex socio-ecological problems of forestry to mere issues of public order and the recovery of state revenue. In conclusion, this Presidential Regulation creates a structural and philosophical anomaly that risks being a symptomatic solution, ignoring root problems such as tenurial conflicts and systemic corruption, and potentially degrading civilian supremacy in natural resource governance.